The Effect of Discipline and Work Environment on Public Satisfaction Mediated by The Quality of Public Services at The Population and Civil Registration Service of West Tanjung Jabung Regency - Nopri Yanto; M. Zahari; Osrita Hapsara (Greenation International Journal of Economics and Accounting, 2025)
This study aims to analyze the influence of work discipline and the work environment on public satisfaction, with the quality of public services as a mediating variable at the Population and Civil Registration Office of West Tanjung Jabung Regency. This study used a quantitative approach with a survey method. The population in this study was all 57,405 users of population administration services at the Population and Civil Registration Office of West Tanjung Jabung Regency. The sample size was determined using the Slovin formula with a 10% error rate, resulting in a sample size of 100 respondents. Data collection was carried out through a questionnaire with a Likert scale. The independent variables in this study were work discipline and the work environment, the mediating variable was the quality of public services, and the dependent variable was public satisfaction. Data analysis was performed using path analysis with Partial Least Squares (PLS-SEM) to test the direct and indirect effects between variables. The results showed that work discipline and the work environment had a positive and significant effect on the quality of public services. Furthermore, the quality of public services significantly influenced public satisfaction and was able to mediate the influence of work discipline and the work environment on public satisfaction. These findings confirm that increased public satisfaction can be achieved through improved employee discipline and a supportive work environment, with the quality of public services as a key connecting factor.